2016
DOI: 10.1098/rspb.2016.0375
|View full text |Cite
|
Sign up to set email alerts
|

Unique pattern of dietary adaptation in the dentition of Carnivora: its advantage and developmental origin

Abstract: Carnivora is a successful taxon in terms of dietary diversity. We investigated the dietary adaptations of carnivoran dentition and the developmental background of their dental diversity, which may have contributed to the success of the lineage. A developmental model was tested and extended to explain the unique variability and exceptional phenotypes observed in carnivoran dentition. Carnivorous mammalian orders exhibited two distinct patterns of dietary adaptation in molars and only Carnivora evolved novel var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(64 citation statements)
references
References 47 publications
(108 reference statements)
3
60
0
1
Order By: Relevance
“…Asahara (2013) and Asahara et al (2016) reported that the relative molar size was reflective of the diet among species of canids. The more carnivorous canid species (such as Canis lupus ) possess low M 2 /M 1 scores and the more omnivorous species (such as N. procyonoides or U. cinereoargenteus ) have higher scores (Asahara, 2013; Asahara et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Asahara (2013) and Asahara et al (2016) reported that the relative molar size was reflective of the diet among species of canids. The more carnivorous canid species (such as Canis lupus ) possess low M 2 /M 1 scores and the more omnivorous species (such as N. procyonoides or U. cinereoargenteus ) have higher scores (Asahara, 2013; Asahara et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The more carnivorous canid species (such as Canis lupus ) possess low M 2 /M 1 scores and the more omnivorous species (such as N. procyonoides or U. cinereoargenteus ) have higher scores (Asahara, 2013; Asahara et al, 2016). In addition, the insectivorous hoary fox Lycalopex vetulus has higher M 2 /M 1 and M 3 /M 1 scores than almost all other omnivorous species, and the insectivorous bat-eared fox O. megalotis has higher M 2 /M 1 and M 3 /M 1 scores than all other canids, indicating very low inhibition and high activation during molar development (Asahara, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations